Promoting physical activity in vulnerable adults ‘at risk’ of homelessness: a randomised controlled trial protocol - Sarah E Jackson; Lee Smith; Charlotte Stringer; Mike Loosemore; Eloise Moller; Guillermo Felipe López-Sánchez; Joseph Firth; James Johnstone; Brendon Stubbs; Davy Vancampfort (BMJ Open)
Introduction People who are homeless, or at risk of homelessness, have substantially poorer health. Sustained and regular participation in physical activity is beneficial for both mental and physical health. Limited data suggest that levels of physical activity in the homeless and those at risk of homelessness are low, and access to community-based exercise is limited or non-existent for this population. Nonetheless, exercise programmes for the homeless could provide a feasible and scalable intervention for providing beneficial effects on physical and mental health in this population. The primary aim of this study is to evaluate the impact of a group exercise intervention on activity levels in people who are homeless or at risk of homelessness in central London, UK. The secondary aim is to evaluate the impact of the intervention on mental and physical health outcomes.Method and analysis A 2-arm, individually randomised controlled trial in people who are homeless and those vulnerable and at risk of homelessness in central London, UK. Participants will be recruited through a London-based homeless charity, Single Homeless Project. Following baseline assessments and allocation to intervention (exercise classes) or control (usual care), participants will be followed up at 3, 6, 9 and 12 months. The primary outcomes will be change in objective physical activity. The secondary outcomes will include change in fitness assessments and mental health parameters. Changes in drug use and alcohol dependency will also be explored.Ethics and dissemination Ethical approval to process and analyse data and disseminate findings was obtained through the Anglia Ruskin University Department of Sport and Exercise Sciences Research Ethics Committee. Results of this study will be disseminated through peer-reviewed publications and scientific presentations.